"Gaining a new sense of me": Mature students experiences of under-graduate nursing education. (January 2021) - Christensen, Martin; Craft, Judy
Abstract: Background: Mature aged students bring a unique perspective to the under-graduate nursing programme. For many this will be the culmination of different career pathways or the feeling it is their time. However, mature students also experience significant changes both educationally, familial and financially. Balancing the competing demands can create a great deal of emotional and stressful challenges. Aim: To gain a better understanding of the mature aged student's educational experiences of undertaking the bachelor of nursing degree. Setting: The setting included a regional and metropolitan campus in South East Queensland. Participants: A convenience sample of mature nursing students (n = 21) were asked to participate in focus group interviews. Method: Five focus group interviews were transcribed and analysed using inductive thematic analysis. There were three themes captured from the focus group interviews – Family Supported/Family Divided; Challenges for the Older Student and Gaining a New Sense of Me. Results: Many of the mature students in this study cherished the idea of making a new start and a nursing career afford them the opportunity – it was something they had always dreamed of. They expressed the challenges associated with being a nursing student, the competing demands – financial, social and educational, but despite these they saw their future as being extremely positive and potentially rewarding. Conclusions: Mature aged students continue to experience difficult academic challenges, difficult life choices especially where family support is not forth-coming and at times financial insecurity. It would seem reasonable that ensuring the educational experience is tailored to meet the challenges of being a mature student are considered to support the additional expenditure that is created by returning to higher education. Highlights: Mature nursing students commencing tertiary education experience a number of competing demands and challenges. These challenges include financial insecurity, technological capability and family expectations. Meeting these challenges took ingenuity, flexibility and negotiation. Despite the challenges, many felt it was their time to do something altruistically rewarding.